The WHO’s critical bacteria list: scientific response eight years after its implementation and development of an AI-based tool for its monitoring - Almonacid, Juan Eduardo Robledo (2025)
Fil: Almonacid, Juan Eduardo Robledo. Universidad Nacional de Córdoba. Facultad de Ciencia Químicas. Departamento de Ciencias Farmacéuticas. Farmacognosia; Argentina